A Contribution of Microfinance in Women Empowerment: A Case of Janakpur Municipality, Nepal - Chaudhary, Manoj Kumar (International Research Journal of MMC, 2022)
Microfinance has been one of the major sources of financing for financially backward society in the rural part of Nepal. The economic demography has also been found updated recently through the women empowerment movement. Hence, the study mainly looks into the role and importance of microfinance in the women empowerment movement in the rural part of Nepal like Janakpur. The study found that the general awareness regarding the importance and role of microfinance has been updated. However, the decision making authority is still under the control of Elder Male members of the house. The researcher came to the conclusion that the microfinance has been playing an exemplary role in the field of women empowerment in Janakpur. However, there are still some rooms for improvement in the policy and operation of microfinance.